2019
DOI: 10.1016/j.biomaterials.2019.04.009
|View full text |Cite
|
Sign up to set email alerts
|

The cell in the ink: Improving biofabrication by printing stem cells for skeletal regenerative medicine

Abstract: Recent advances in regenerative medicine have confirmed the potential to manufacture viable and effective tissue engineering 3D constructs comprising living cells for tissue repair and augmentation. Cell printing has shown promising potential in cell patterning in a number of studies enabling stem cells to be precisely deposited as a blueprint for tissue regeneration guidance. Such manufacturing techniques, however, face a number of challenges including; (i) post-printing cell damage, (ii) proliferation impair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
172
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 188 publications
(174 citation statements)
references
References 105 publications
2
172
0
Order By: Relevance
“…For instance, a hyper-elastic bone (HB) construct printed with a blend made of poly(lactic-co-glycolic acid), polycaprolactone and hydroxyapatite (PLGA/PCL/HAp) has recently shown promising potential for in vivo application [4]. Human bone marrow stromal cells (HBMSCs) have been found to actively participate in bone repair when encapsulated in functional hydrogel networks [5,6] indicating the promise of cell-based strategies to closely recapitulate tissue architecture and functions. As bioprinted tissues promote regeneration in vivo, the tissue should be amenable to remodelling, facilitating the formation of structures driven by cellular and physiological requirements [7].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, a hyper-elastic bone (HB) construct printed with a blend made of poly(lactic-co-glycolic acid), polycaprolactone and hydroxyapatite (PLGA/PCL/HAp) has recently shown promising potential for in vivo application [4]. Human bone marrow stromal cells (HBMSCs) have been found to actively participate in bone repair when encapsulated in functional hydrogel networks [5,6] indicating the promise of cell-based strategies to closely recapitulate tissue architecture and functions. As bioprinted tissues promote regeneration in vivo, the tissue should be amenable to remodelling, facilitating the formation of structures driven by cellular and physiological requirements [7].…”
Section: Introductionmentioning
confidence: 99%
“…Adult human stem cells and human pluripotent stem cells (PSCs) are ideal source materials for different targeted biological applications involving 3D bioprinting. Mesenchymal stem cells (MSCs) will not be considered further in this section, and we refer the reader to a very comprehensive review by Cidonio et al 346 Rather, we will focus in this section on PSCs. Human embryonic stem cells (hESC) are stem cells derived directly from the inner cell mass of preimplantation embryo, 347 which in humans comprises less than a dozen cells found at day 5–6 of development.…”
Section: Pluripotent Stem Cells and Bioprintingmentioning
confidence: 99%
“…The first step has to be to encapsulate PSCs, most commonly in a natural or synthetic hydrogel. 346 , 361 This hydrogel needs to both provide biochemical signals and the right level of physical support. As previously mentioned, natural hydrogels have the advantage that they can consist of decellularized organ-specific ECM components 362 , 363 bearing epitopes which interact with the PSC receptor system (e.g., integrins and their associated transduction machinery) and they generally support PSC maintenance or differentiation.…”
Section: Pluripotent Stem Cells and Bioprintingmentioning
confidence: 99%
“…Similar challenges exist as with extrusion bioprinting apply, namely cell damage during and after printing, stability of the printed structures, and print fidelity and resolution. Recent review of inkjet printing and related bioinks can be found here [55][56][57][58].…”
Section: Inkjet Printingmentioning
confidence: 99%